Tumor lamination in mediastinal giant tumors - KALLAS,ELIAS (2017)
ABSTRACT Mediastinum tumors may grow slowly and reach giant proportions without symptoms, hindering surgical removal. Tumor big dimensions difficult surgical maneuvers, with risk of uncontrollable bleeding and prejudice to surrounding structures. It may be necessary the use of exceptional measures such as venous-venous circulatory deviation, pre-operatory embolization and total extracorporeal circulation. We describe the technique of tumor lamination that allows for complete or almost complete resection of such tumors that in many occasions are not resectable. The description is based on the results of four patients treated with mediastinum giant tumors.